ДЕЯКІ ОСОБЛИВОСТІ ЗАДАЧІ МАКСИМІЗАЦІЇ МОМЕНТУ ВЕКТОРНО-КЕРОВАНИХ АСИНХРОННИХ ДВИГУНІВ У РЕЖИМІ ОСЛАБЛЕННЯ ПОЛЯ - Приймак, Б.І. (Інститут електродинаміки Національної академії наук України, 2017)
The features of torque maximization of vector-controlled induction motors with field weakening are studied. An analytical expression is obtained for the boundary speed of the rotor with which the flux reduction should begin. It has been established that the boundary speeds that distinguish the zones of the torque optimization with different conditions for extremum determining depend strongly on the stator current maximum. If the stator current limitation exceeds the critical value, the optimization zone B, where both voltage and current are limited, disappears, and zones A and C remain where only the current and voltage are limited. In this case, the index of  relative torque increase of the motor, which determines the degree of improvement in the drive properties due to the torque  maximization, ceases to grow. For the calculations we used data from two motors whose power is twenty times different. References 10, figures 6, table.